Women's perceptions of factors needed to encourage a culture of public breastfeeding: a cross-sectional study in Sweden, Ireland and Australia - Charlotta Dykes; Pernilla Ny; Yvonne L. Hauck; Lesley Kuliukas; Louise Gallagher; Vivienne Brady; Christine Rubertsson (BMC, 2023)
Abstract Background Breastfeeding in the public sphere is known to be experienced as a problem for many women. It has been shown to arouse negative feelings among the public, depending on the attitude of those in the immediate surroundings. This contributes to the fact that many women hesitate to breastfeed in public and prepare themselves for potential adverse comments. Methods An online survey was used for an international cross-sectional study including women living in Sweden (n = 1252), Australia (n = 7602) and Ireland (n = 1597). Women who had breastfed within the previous two years were invited to participate through Facebook. One key open-ended question was presented, inviting women to respond to: "What do you think is important or needed to encourage a breastfeeding culture where breastfeeding in public is seen as normal?" During 2018, data were collected during a four-week period. A thematic analysis of women's responses was conducted separately in each country and then comparison and negotiation occurred once similarities between themes and subthemes were confirmed. Frequencies of subthemes were then determined and compared between the three countries. Results Seven subthemes developed from the data; 'Make breastfeeding visible in society'; 'Healthcare professionals support and knowledge regarding breastfeeding'; 'Education of the public'; 'Inviting environment'; 'Zero tolerance to other's unwanted opinions'; 'Focusing on the needs and rights of the breastfeeding dyad'; and 'Desexualize breastfeeding and women's' bodies in society'. Subthemes were integrated under two themes; 'Active supportive interventions needed for breastfeeding' and 'The obvious right of breastfeeding women and children to take a seat in the public sphere'. Conclusion The common experience that exists today regarding public breastfeeding requires change towards normalization. Further collaborative research is recommended to meet the expressed requirements from women who wish to breastfeed in public.